CHANGE OF CURRICULUM AND ITS IMPLICATION ON TEACHERS' PERFORMANCE IN EFL CLASSROOM - Absharini Kardena (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Changes of curriculum commonly face such resistances by educational practitioners. The resistances commonly appear because the changes of curriculum give impacts not oniy on aims of education, but also on the process of its implenrentation. During the process of implementing a new curriculum, many aspects are intluenced. such as syllabi, teaching materials, teaching techniqr:e and so on that shortly deal with teachers' performance. Thus, teachers are demanded to acclimatize with any changes on the new curriculum. Theteachers as one ofeducational practitioners are required to have a depth- understanding on running a new process of EFL classroom as demanded by the new curriculum. Thus, teachers' understanding about the new curriculum is so essential since it directly inf'luenc€s their performance in the classroom. This article, which is derived and further developed based on research conducted in 2013, discusses and analyzes how the change of curriculum in Indonesia affects teacher's performance on EFL classroom even when it has been implemented for years. It specifically explains teachers' performance in implementing school-based curriculum; rvhether the teachers' performance has been in line with aims and goals ofschool-based curriculum or it needs further development.